Posibilitas Penerapan In Rem Asset Forfeiture Sebagai Upaya Asset Recovery Di Indonesia - Fitriyani, Desi; Maizaroh, Muthi’ah (AML/CFT Journal : The Journal Of Anti Money Laundering And Countering The Financing Of Terrorism, 2023)
Improving the method of asset confiscation to recover state losses is an urgent issue that needs to be addressed. The current approach, which relies on in-person procedures, presents numerous ongoing obstacles. Therefore, a breakthrough in asset confiscation is required, namely implementing in rem asset forfeiture. This paper explores the feasibility of adopting in-rem asset forfeiture in Indonesia while addressing the associated challenges. It is both descriptive and prescriptive, providing an analysis of how to establish a comprehensive regulatory framework to optimize asset confiscation. The research employs a normative juridical research method, focusing on the concept and legal policies on asset confiscation. The findings suggest the need to revamp the legal system governing asset confiscation in Indonesia by officially incorporating in rem asset forfeitures into positive law and achieving vertical and horizontal legal harmonization.